Implications of Learning About Japanese Language and Culture for the Japanese Department Alumni Living in Japan - Kania Izmayanti, Dewi; Syahrial, Syahrial; Sri Wahyuni, Nolia (KnE Social Sciences, 2022)
Working in Japan is one of the goals of students in the Japanese Department, due to Japan’s strong appeal. Is the material learned in this department enough to help the alumni diaspora in living their lives? The purpose of this study was to describe the implications of learning about the Japanese language and culture for the lives of the alumni of the Japanese Department living in Japan. Qualitative descriptive methods were used, with data collected through questionnaires. The analytical technique used was interpretative description. The results found that the language and culture learned during the lectures was quite helpful in living in Japan. The speaking courses (kaiwa) were highly used. Furthermore, the materials provided in the courses on Japanese grammar (Bunpo), Japanese society, public communication, management and work ethic, as well as conversation, were felt to be very helpful in living in Japan. This was evident from the understanding of the Japanese language used by diaspora alumni in communicating with Japanese people. In addition, the alumni diaspora did not experience obstacles in living in Japan. From these findings it can be concluded that learning about Japanese language and culture was very helpful for the alumni diaspora living in Japan. Keywords: implications, learning, diaspora, alumni